PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN DI LINGKUNGAN INSITUT AGAMA ISLAM NEGERI PALANGKA RAYA - Muhammad Riza Hafizi (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This study aims to analyze the effect of workload on employee performance within the State Islamic Institute of Palangka Raya. Performance is a description of the level of achievement of the implementation of a program of activities or policies in realizing the goals, objectives, vision, and mission of the organization as outlined through an organization's strategic planning. This research was conducted on 92 employees who work in IAIN Palangka Raya.The research findings indicate that the workload variable has a positive effect on employee performance in the State Islamic Institute of Palangka Raya. This is evidenced by the results of the regression test statistics obtained a value of (β) 0.778 (p 0.05; p = 0.000). With an R square adjust the value of 34%. then this study successfully demonstrated that workload has a positive and significant influence on performance. Hypothesis testing uses the help of the Statistical Package for the Social Sciences program.